Iran : politics, history and literature - Katouzian, Homa. ([S.l.] : Routledge, 2013)
This book offers a view of Iran through politics, history and literature, showing how the three angles combine. Iran, being a revolutionary society, experienced two great revolutions within the short span of just seventy years, from the 1900s to the 1970s. Both were massive revolts of the society against the state; the main objective of the first being to establish lawful government to make modernisation possible, and the second, to overthrow the absolute and arbitrary state, though this time mainly under the banner of religion and Marxism-Leninism and anti-Westernism. Neither of them succeeded in their lofty ideals for reasons that are explained and analysed within. The author also offers a detailed description of Iran$1 (Bs short-term society, examining the political and intellectual lives of two of the most remarkable intellectuals-cum-politicians of the twentieth century. This book provides an overview of modern Persian literature, both poetry and prose, and discusses the works of three of the most remarkable Persian poets and writers of the period. It considers classical Persian literature through the great variety of its form and substance, and neo-classical literary developments in the nineteenth century, covering the whole history of Persian literature. This is crowned in the last chapter by the love poetry of one of the greatest Persian poets. Iran will be of interest to students and scholars of Iranian studies and Middle East Politics.s
Keywords: Civilization; Iran; Persian literature; Political science